2008
DOI: 10.1007/s00056-008-0716-7
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Changes in the Treatment of Class III Using the Fränkel Appliance*

Abstract: According to these study results, FR-3 treatment has an obvious effect on maxillary development, and affects the shape and, to a certain degree, the position of the mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(48 reference statements)
0
11
0
1
Order By: Relevance
“…The best improvement of the ANB, SNA and SNB angles was in the Kajiyama study (+7·83°, +4·16°, −3·66°). The biggest increase of maxillary length (+4·4 mm) was in Falck and Zimmermann‐Menzel's study using FR‐III, while with RME+FM the greatest increase was reached in Vaughn's study (+4·29 mm). The highest control of mandibular length was in the Yagci and Uysal study with RME+FM (−6·4 mm).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…The best improvement of the ANB, SNA and SNB angles was in the Kajiyama study (+7·83°, +4·16°, −3·66°). The biggest increase of maxillary length (+4·4 mm) was in Falck and Zimmermann‐Menzel's study using FR‐III, while with RME+FM the greatest increase was reached in Vaughn's study (+4·29 mm). The highest control of mandibular length was in the Yagci and Uysal study with RME+FM (−6·4 mm).…”
Section: Resultsmentioning
confidence: 79%
“…Regarding vertical changes 6 of 21 studies showed a counterclockwise rotation of the mandible or stability of patient divergence . The greatest counterclockwise rotation was in Falck's study with a reduction of the gonial angle of −7·17° and of −5·15° for the mandibular plane angle. On the other hand, 15 studies reported a significant increase in mandibular divergence.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations